Działania zbiorowe w perspektywie przedtransformacyjnej - Chumiński, Jędrzej (Collective actions in the pretransformational perspective, 2005)
Collective actions are a domain of civic communities. Their realization is possible only within democratic systems, where basic civil rights are respected. In totalitarian states, where each case of uncontrolled individual action is seen as a threat for the foundations of the system, collective actions are in fact out of the question. On the other hand, if we consider the history of actual totalitarian regimes, the extent to which their total ambitions concerning the authoritative control over community were realized, usually was a far cry from the desired model. Even in extremely difficult conditions a considerable group of citizens was ready to fight for their identity. Such actions were propelled by e.g. previous individual experience, level of education, religious norms, cultivation of traditional values, authority of a family circle, active approach of individuals or social groups. Polish industrial workers are an example of a social group which undertook collective actions under conditions of monocentrical order. The article analyses how these actions differed depending on the biosocial traits and axiological norms of this environment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1090, s. 64-95